Clinical presentations associated with SARS-CoV-2 in a Covid pediatric intensive care unit of a national hospital in Lima: Presentaciones clínicas asociadas al SARS-CoV-2 en una unidad de cuidados intensivos pediátricos Covid de un hospital nacional de Lima - Paricahua, Edgar Coila (2021)
The coronavirus disease 2019 (COVID-19) affects more adults than children. Later, the Pediatric Multisystemic Inflammatory Syndrome (SIMS) associated with SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) was described, whose peak incidence was 4 weeks after the maximum peak of infections, so it is postulated that it is a post-infectious entity, and is characterized by affecting several organs and systems. In response to this new need, the Pediatric Intensive Care Unit (PICU) of the Edgardo Rebagliati Martins National Hospital set up a differentiated environment with two beds for the care of children with SARS-CoV-2 infection, to reduce the risk of in-hospital infections.